Unravelling the proteomic signature of extracellular vesicles released by drug-resistant Leishmania infantum parasites. - Noélie Douanne; George Dong; Mélanie Douanne; Martin Olivier; Christopher Fernandez-Prada (Public Library of Science (PLoS), 2020)
Leishmaniasis constitutes the 9th largest disease burden among all infectious diseases. Control of this disease is based on a short list of chemotherapeutic agents headed by pentavalent antimonials, followed by miltefosine and amphotericin B; drugs that are far from ideal due to host toxicity, elevated cost, limited access, and high rates of drug resistance. Knowing that the composition of extracellular vesicles (EVs) can vary according to the state of their parental cell, we hypothesized that EVs released by drug-resistant Leishmania infantum parasites could contain unique and differently enriched proteins depending on the drug-resistance mechanisms involved in the survival of their parental cell line. To assess this possibility, we studied EV production, size, morphology, and protein content of three well-characterized drug-resistant L. infantum cell lines and a wild-type strain. Our results are the first to demonstrate that drug-resistance mechanisms can induce changes in the morphology, size, and distribution of L. infantum EVs. In addition, we identified L. infantum's core EV proteome. This proteome is highly conserved among strains, with the exception of a handful of proteins that are enriched differently depending on the drug responsible for induction of antimicrobial resistance. Furthermore, we obtained the first snapshot of proteins enriched in EVs released by antimony-, miltefosine- and amphotericin-resistant parasites. These include several virulence factors, transcription factors, as well as proteins encoded by drug-resistance genes. This detailed study of L. infantum EVs sheds new light on the potential roles of EVs in Leishmania biology, particularly with respect to the parasite's survival in stressful conditions. This work outlines a crucial first step towards the discovery of EV-based profiles capable of predicting response to antileishmanial agents.